2019
DOI: 10.1111/ele.13215
|View full text |Cite
|
Sign up to set email alerts
|

Climate variation influences host specificity in avian malaria parasites

Abstract: Parasites with low host specificity (e.g. infecting a large diversity of host species) are of special interest in disease ecology, as they are likely more capable of circumventing ecological or evolutionary barriers to infect new hosts than are specialist parasites. Yet for many parasites, host specificity is not fixed and can vary in response to environmental conditions. Using data on host associations for avian malaria parasites (Apicomplexa: Haemosporida), we develop a hierarchical model that quantifies thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 102 publications
(214 reference statements)
3
108
0
2
Order By: Relevance
“…Whereas these host traits are often phylogenetically conserved, they may also be influenced by environmental conditions. Therefore, rather than host ecology and evolution, regional climate determined primarily by temperature seems to have an important impact on Leucocytozoon host range expansion as demonstrated recently for its two related genera (Fecchio, Wells, et al, 2019).…”
Section: The Highest Probability Of a Bird Being Infected Withmentioning
confidence: 86%
See 2 more Smart Citations
“…Whereas these host traits are often phylogenetically conserved, they may also be influenced by environmental conditions. Therefore, rather than host ecology and evolution, regional climate determined primarily by temperature seems to have an important impact on Leucocytozoon host range expansion as demonstrated recently for its two related genera (Fecchio, Wells, et al, 2019).…”
Section: The Highest Probability Of a Bird Being Infected Withmentioning
confidence: 86%
“…For each of the 69 sampling sites in our dataset, we extracted altitude as well as several long‐term climate variables that could relate to Leucocytozoon infection prevalence by influencing the distributions and densities of vectors (see Appendix S1). Previous studies have found evidence that temperature and precipitation variables, particularly those that capture variation in summer and winter climates, may be linked to important aspects of haemosporidian community assembly and transmission (Clark et al, ; Fecchio, Wells, et al, ; Oakgrove et al, ; Sehgal et al, ). We included maximum temperature of the warmest month, maximum rainfall of the wettest month, minimum temperature of the coldest month and minimum rainfall of the driest month as predictors in our analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that environmental variation can affect the host specificity of parasites in other systems as well, including avian malaria parasites Plasmodium and Haemoproteus spp. (Fecchio et al 2019). The short life cycles of vector-borne pathogens will lead them to experience environmental variation (host availability) mostly at the among-generation level.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that environmental variation can affect the host specificity of parasites in other systems as well, including avian malaria parasites Plasmodium and Haemoproteus spp. (Fecchio et al ). The short life cycles of vector‐borne pathogens will lead them to experience environmental variation (host availability) mostly at the among‐generation level.…”
Section: Discussionmentioning
confidence: 99%